Preterm singleton breech delivery in a teaching hospital of Saudi Arabia: Vaginal versus cesarean delivery - Turki G Gasim (Wolters Kluwer Medknow Publications, 2008)
Objectives:The aim of this study was to determine the incidence of singleton preterm breech babies born in a teaching hospital, and to study the influence of the mode of delivery on perinatal outcome in preterm births with breech presentation. Methods: A retrospective analysis from the medical records of patients who had preterm singleton breech delivery (24 - 36 weeks gestation) was undertaken in a tertiary care hospital in the Eastern province of Saudi Arabia between January 1992 and December 2001. All the patients with intrauterine fetal death, multiple pregnancies and lethal congenital fetal malformations were excluded from the study. Intrapartum and neonatal morbidity and mortality in vaginal versus cesarean delivery groups were the main outcomes measured. Results: Of 24,708 deliveries that occurred in the hospital during the period of study, there were 195 preterm singleton breech deliveries, giving an incidence of 0.08%. One hundred and forty-eight (75.9%) patients delivered vaginally and did not have any medical or obstetric complications. Forty-seven (24.1%) patients underwent caesarean section. While the neonatal morbidity was similar in the two groups, the neonatal mortality was significantly higher for vaginal delivery than cesarean section (p<0.00069). Conclusion: In view of the significantly higher neonatal mortality found in vaginal delivery, the present study favors abdominal delivery for a singleton preterm breech fetus.